The syntax of Isamal language: The Principles and Parameters Theory - Rodney C. Jubilado (Journal of Modern Languages)
The current study presents a syntactic analysis of the indigenous language of Isamal of the Samal Islands of Davao Gulf in Mindanao, Southern Philippines. This study analyzes the Isamal verbs and the syntactic projection of Isamal verbs using the Principles and Parameters Theory. It aims to establish the categorical and semantic selections of !samal verbs, determine the argument/thematic structure of Isamal verbs and represent the syntactic structure of the argument/thematic structure of Isamal verbs.